Lógicas institucionais e estratégia como prática: uma abordagem construtivista - Viana, Marcelo Ferreira (2016)
In this dissertation, we aimed at apprehend the strategy construction process as practice, emphasizing the implication of logic hybridism over organizational practices in a Higher Education Institution (HEI). More specifically, we sought to: i- Describe the trajectory of the studied HEI, individualizing the institutional logics that mark its insertion into the socio-educational context; ii- Investigate the strategy construction process, demonstrating the practices institutionalized by the HEIs in response to the hybridism of institutional logics; iii- Analyze the participation process of different actors in the construction of strategies as practices, highlighting its interpretations surrounding the hybridism of institutional logics. For this, the theoretical framework was constructed based on the understanding of strategy for the Institutional Theory, from the perspective of Strategy as Social Practice and from the hybrid arrangement of Institutional Logics, as well as the dialog between these views. Using a case study methodology, the data collected from documents, interviews, participant observations, website contents and recorded archives were analyzed. By means of an empirical investigation, it was possible to understand, from the perspective of a more integrated practice, that it is important to examine the different practices within the context in question, giving attention to how is responsible for its development and how they are ratified within the chosen institution. While recovering the history of the institution, we perceived that many institutional practices are strongly influenced by State logics. Thus, certain institutional actors are responsible for promoting the dialog participation and deliberative argumentation along with other collaborators that will, therefore, give continuity to ratifying the practices inserted into their respective actin locus. While acting, the agents resort to many other logics, asserting the institutional logics of family, religion, market, professions, corporations, legal -institutional, which makes the process of ratifying new practices extremely complex. The main perceptions regarding the different practices, be them structural, adaptation, administrative, reflection, diversification and expansion, regulation, reorganization, planning and management, among others, associated to strategies resultant of institutional adaptation, socio-educational demands and financial support, indicate that a set of practices present singularities and differences when exposed to the hybrid arrangement of institutional logics. In this case, we defend that strategies as practices have caused a series of social effects and transformations over the history of the organization and, it was only possible to identify this, by means of understanding the operative practice under the influence of the hybrid arrangement of institutional logics.